Cultural Diversity in Popular Responses to the Rorschach test in Asháninka Children and Rural Cusco Children - Jara, Lupe (2017)
The popular response is one of the Rorschach Comprehensive System codes most sensitive to cultural impact. This study seeks to establish the popular responses provided by 108 children, ages from 6 to 11, 58 asháninkas and 50 children from two rural areas in Cusco. The results show that there are three popular responses: the whole animal (D1, plate VIII, 54.63%), the butterfly (W, plate V, 44.44%) and the bat (W, plate V, 37.04%). At the same time, there are differences in the number and content of the popular response according to community, gender, age and the evaluator.